2009
DOI: 10.1128/jvi.01083-09
|View full text |Cite
|
Sign up to set email alerts
|

Passage of Dengue Virus Type 4 Vaccine Candidates in Fetal Rhesus Lung Cells Selects Heparin-Sensitive Variants That Result in Loss of Infectivity and Immunogenicity in Rhesus Macaques

Abstract: Dengue virus (DENV) infects humans via the bite of infected mosquitoes, principally Aedes aegypti. DENV infections can be asymptomatic or cause a spectrum of illnesses that range from mild dengue fever to a severe, life-threatening disease characterized by dengue hemorrhagic fever/dengue shock syndrome (13, 38). The four DENV serotypes (DENV type 1 [DENV-1] to DENV-4) are the most important members of the genus Flavivirus in terms of morbidity, geographic distribution, and socioeconomic burden (1, 12). Several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 57 publications
3
41
1
Order By: Relevance
“…These data clearly demonstrated that the reduction of DENV binding to heparan sulfate in neuronal cells decreases DENV infectivity in neuronal cells. In contrast to the results of our study, two reports demonstrated the reduction of DENV binding to heparan sulfate leads to the increase of DENV infectivity in hosts (47,48). Añez et al (48) reported that s.c. infection of primates with a DENV-4 mutant that has high binding affinity for heparin resulted in a reduced infectivity; similarly, Prestwood et al (47) showed that mice infected i.v.…”
Section: Discussioncontrasting
confidence: 55%
“…These data clearly demonstrated that the reduction of DENV binding to heparan sulfate in neuronal cells decreases DENV infectivity in neuronal cells. In contrast to the results of our study, two reports demonstrated the reduction of DENV binding to heparan sulfate leads to the increase of DENV infectivity in hosts (47,48). Añez et al (48) reported that s.c. infection of primates with a DENV-4 mutant that has high binding affinity for heparin resulted in a reduced infectivity; similarly, Prestwood et al (47) showed that mice infected i.v.…”
Section: Discussioncontrasting
confidence: 55%
“…The protection against live virus challenges also correlates with anamnestic neutralizing antibodies detected on days 15 and 30 post-challenges. Taken together, the present study demonstrated that the E-E 345 K mutation from MRC-5 cells can still induce potent immunogenicity in rhesus monkeys as compared to the complete loss of monkey immunogenicity by the E-E 327 G mutation reported from FRhL cell passage [11]. These results suggest that the DENV-4 E-E 345 K mutant propagated in MRC-5 cells may have potential for the use in live-attenuated DENV vaccine development.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to other flaviviruses, DENV undergo adaptive mutations involving heparan sulfate binding for growth selection in FRhL, BHK and Vero cells [11], [15], [16]…”
Section: Discussionmentioning
confidence: 99%
“…The surface potential on DENV2 showed larger continuous patches of positive charges compared to those for DENV1 and DENV4, and this may facilitate enhanced binding to heparan sulfate. It has been shown previously that passaging virus in certain cell lines (FRhL, SW13, and BHK21) may increase its affinity for heparan sulfate (32,33). If this is the case, then the comparison between DENV2 and DENV4 with different passage histories might not be valid.…”
Section: Resultsmentioning
confidence: 80%